2010
DOI: 10.1111/j.1365-2516.2008.01962.x
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of factor VIII‐specific memory B cells

Abstract: Summary. The development of inhibitory antibodies against factor VIII (FVIII) is the major complication in patients with haemophilia A who are treated with FVIII products. Memory B cells play an essential role in maintaining established antibody responses. Upon re-exposure to the same antigen, they are rapidly re-stimulated to proliferate and differentiate into antibody-secreting plasma cells (ASC) that secrete high-affinity antibodies. It is, therefore, reasonable to believe that memory B cells have to be era… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
28
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 46 publications
1
28
0
Order By: Relevance
“…This mechanism depends on induction of Tregs, and the continued presence of these cells is required to maintain tolerance. The high expression of F.IX in mice following hepatic gene transfer (~20-40% of normal) may also be responsible for this rapid clearance of F.IX-specific antibodies due to suppression of memory B cells (4, 51). Though this phenomenon is understandably difficult to verify in human studies, it is encouraging that, to date, none of the patients treated with a liver-directed AAV vector have formed a F.IX-specific immune response (52, 53).…”
Section: Gene Therapies For Hemophlia Bmentioning
confidence: 99%
“…This mechanism depends on induction of Tregs, and the continued presence of these cells is required to maintain tolerance. The high expression of F.IX in mice following hepatic gene transfer (~20-40% of normal) may also be responsible for this rapid clearance of F.IX-specific antibodies due to suppression of memory B cells (4, 51). Though this phenomenon is understandably difficult to verify in human studies, it is encouraging that, to date, none of the patients treated with a liver-directed AAV vector have formed a F.IX-specific immune response (52, 53).…”
Section: Gene Therapies For Hemophlia Bmentioning
confidence: 99%
“…To further validate Gal-9 as a new MSC-driven immune regulator, we extended our investigation and analyzed MSCs and Gal-9 in vivo in a disease model of allo immunization. Immunization against FVIII is the most frequent complication in hemophilia A treatment and FVIII triggers a profound IgG response in mice [54]. Because Rafei et al [55] demonstrated that MSC application support the clearance of anti-FVIII titers in mice, we wanted to know whether activated MSCs were capable of suppressing FVIII immune response simultaneously.…”
mentioning
confidence: 99%
“…Therefore, it is paramount to treat patients with high-titer inhibitory antibodies with effective strategies to reduce and best eliminate pre-existing inhibitory antibodies before attempting tolerance induction. Blockade of co-stimulatory pathway has been shown to prevent FVIII-specific murine memory B cells from becoming re-stimulated by FVIII in vitro and in vivo[37]. In our previous experiments, we have demonstrated that the combination treatment of IL-2/IL-2mAb complexes + rapamycin + anti-CD20 + FVIII reduced FVIII-specific memory B cells and ASCs from the spleen, leading to transient decreases of pre-existing neutralizing antibody titers [17].…”
Section: Discussionmentioning
confidence: 99%